Propagation Characteristics of Explosive Waves in Layered Media Numerical Analysis - Changjing, Xia; Yongxiang, Dong; Liping, Chen; Dongjie, Xue; Shunhong, Wang (Defence Science Journal, 2009)
The layered media under one-dimensional strain with different wave-impedance materials have been studied. The three typical prototypes have been analysized, including steel plate, aluminum foam, and concrete as the middle layer, and the upper and lower layers are concrete material. The attenuation of the amplitude of stress at different positions, the peak stress and the duration at the dissimilar material interface, and the absorbing energy distribution in different layers for different models have been obtained by numerical simulation. The material of the middle layer with lower impedance can effectively reduce the amplitude of stress, increase the duration of explosive wave, and change the distribution of energy in different layers. But the influence of the middle layer with higher impedance material on layered media is contrary. The middle layer with soft material is the better matching of wave impedance to explosive wave propagation. The analytical conclusions are of great significance for the design of protective structures against the explosion-induced hazards and mine safety protection from outburst and explosion. Defence Science Journal, 2009, 59(5), pp.499-504, DOI:http://dx.doi.org/10.14429/dsj.59.1551